2022
DOI: 10.3390/cancers14225519
|View full text |Cite
|
Sign up to set email alerts
|

CLEFMA Induces the Apoptosis of Oral Squamous Carcinoma Cells through the Regulation of the P38/HO-1 Signalling Pathway

Abstract: The purpose of this research was to evaluate the impact and the underlying molecular mechanism of CLEFMA-induced cell death in human OSCC. The anti-tumour properties of CLEFMA in oral cancer were explored using colony formation, flow cytometry, human apoptosis array, Western blot, and immunohistochemistry assays. The in vivo anti-tumour effect of CLEFMA administered by oral gavage was evaluated using SCC-9-derived xenograft-bearing nude mouse models. CLEFMA significantly suppressed colony formation and elicite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(50 reference statements)
1
2
0
Order By: Relevance
“…49 Nevertheless, up-regulation of HO-1 is also found in drug-mediated tumour apoptosis, especially in head and neck squamous cell carcinoma. Our previous studies have indicated that curcumin analogues increased HO-1 expression in OSCC apoptosis through MAPK pathways, 28,29 which agrees with our present study that HO-1 is overexpressed in hispolon-induced apoptosis.…”
Section: F I G U R Esupporting
confidence: 93%
See 1 more Smart Citation
“…49 Nevertheless, up-regulation of HO-1 is also found in drug-mediated tumour apoptosis, especially in head and neck squamous cell carcinoma. Our previous studies have indicated that curcumin analogues increased HO-1 expression in OSCC apoptosis through MAPK pathways, 28,29 which agrees with our present study that HO-1 is overexpressed in hispolon-induced apoptosis.…”
Section: F I G U R Esupporting
confidence: 93%
“…Human siRNAs for non‐specific control and HO‐1 were obtained from Ambion Inc. The transfection of siRNA was using Lipofectamine RNAi MAX reagent (Invitrogen) by following a previously described process 28,29 . At 48 h after transfection, cells were used for HO‐1 detection by Western blotting assay.…”
Section: Methodsmentioning
confidence: 99%
“…21 CLEFMA possesses superior bioavailability and solubility to those of curcumin; it also exerts antiproliferative effects on cancer cells 8,22 and is a potential active anticancer compound. 23,24 Moreover, CLEFMA was demonstrated to have the potential to induce cell death in lung adenocarcinoma cells. 9 To date, no study has investigated the effect of CLEFMA on cervical cancer cells.…”
Section: Introductionmentioning
confidence: 99%